The putative cardiomyines (Rodentia, Cavioidea) of the middle Miocene of Patagonia (Argentina) and the differentiation of the Family Hydrochoeridae - Vucetich, María Guiomar (2011)
The crown group of Cavioidea sensu stricto (comprises Caviidae (Caviinae [Cuyes] and Dolichotinae [Maras]) and Hydrochoeridae. The latter encompasses the gigantic semiaquatic Hydrochoerinae (Capybaras), the small and rock dweller Kerodon (Mocos), and the extinct Cardiomyinae, a group of large rodents that share with the hydrochoerines ever-growing double-heartshaped cheek teeth with accessory fissures on lingual (lowers) and labial (uppers) walls, enlarged M3 and p4, and a broad palate. In spite of these similarities, cardiomyines were classically classified as Caviidae. The crown group of Cavioidea s.s. is first recorded in the middle Miocene of Colombia with Prodolichotis pridiana. Additionally, Kraglievich, based on two isolated lower molars, described two species from the late middle Miocene of Patagonia that tentatively assigned to the cardiomyine Cardiomys (Cardiomys? huemulensis and C.? andinus). But it is in the early late Miocene when the fossil record shows the Cavioidea s.s. fully differentiated. The most important turnover in the history of caviomorph rodents occurred precisely during the middle Miocene, especially after the Colloncuran age. It involved the extinction of most of the ancient genera as well as the appearance of several new clades usually classified as ?families? and ?subfamilies?. For Cavioidea in particular, this turnover involved the extinction of ?eocardiids? as well as other primitive cavioids on the one hand, and the differentiation of the members of the crown group (Hydrochoerinae, Cardiomyinae, Dolichotinae, and Caviinae) on the other. In this paper we restudy the middle Miocene teeth referred to Cardiomys? by Kraglievich and reanalyze their affinities with other cavioids, their bearing in the comprehension of the evolutionary events occurred during the middle Miocene in Patagonia, as well as the origin and diversification of modern cavioids. We also restudy the holotype of the Chasicoan Procardiomys martinoi, in order to elucidate some doubts on its anatomy and correct definition expressed by Pascual himself, and to understand its bearing in the cardiomyine evolution.